PENGARUH WAKTU PEMANENAN DAN TINGKAT MATURASI DAUN TERHADAP KADAR VITEKSIKARPIN DALAM DAUN LEGUNDI (Vitex trifolia L.) - Yosi Bayu Murti; Indrawan Kurnia Dwinatari (Faculty of Pharmacy, Universitas Gadjah Mada, 2015)
Legundi (Vitex trifolia L.) is one of Indonesia’s traditional crops that have not been studied and developed into fitofarmaka. Legundi leaves can be used for therapy in asthmatics with optimum level. Therefore it is necessary for optimization of harvesting Legundi leaves which includes time and degree of maturation of the leaves. Harvesting time optimization by means of harvesting the leaves at the different times i.e. morning, noon, and evening, while the leaf maturation level optimization by way of harvesting leaves numbered one through five of the youngest end, then the time of harvesting and leaves that provide optimum levels of viteksikarpin were assigned. Measurements of viteksikarpin assigned using TLCdensitometry then analyzed using Wincats software and Microsoft Office Excel 2007. The highest viteksikarpin levels in Legundi leaves harvested in the afternoon, then during the day, and the lowest in the morning. The highest viteksikarpin levels of Legundi leaves were on second leaf, first leaf, third leaf, fourth leaf, and the lowest on fifth leaf. Optimum levels of viteksikarpin in Legundi leaves was harvested in the afternoon by picking the first until the third leaf.